2015
DOI: 10.9734/bjmmr/2015/13461
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Pattern of Genetic Inheritance of Polycystic Ovarian Syndrome

Abstract: Aims: Inheritance of polycystic ovary syndrome (PCOS) is still a controversy. Our study aims to analyze the family history of PCOS features and related metabolic disturbances including the male members to determine the mode of their inheritance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Muralidhara et al in KMC, Mangalore did a study in 2012, where the mean age among patients with PCOS was 27±7.1 which is comparable to our study. 25 In a study done by Spandane et al in 2017, the mean age among PCOS patients was 27±5 which is comparable to the study. 26 In the present study, most of the PCOS patients lived in the urban area 72.8% and in rural area 34%.…”
Section: Discussionsupporting
confidence: 70%
“…Muralidhara et al in KMC, Mangalore did a study in 2012, where the mean age among patients with PCOS was 27±7.1 which is comparable to our study. 25 In a study done by Spandane et al in 2017, the mean age among PCOS patients was 27±5 which is comparable to the study. 26 In the present study, most of the PCOS patients lived in the urban area 72.8% and in rural area 34%.…”
Section: Discussionsupporting
confidence: 70%
“…In a study done by Muralidhara et al in KMC Mangalore in 2012 mean age among PCOS patients was 27+/-7.1 which is comparable to our study. 10 In our study among 100 PCOS patients, 74% were married and 26% were unmarried. Among married women, about 31.1% were parous and 68.9% were nulliparous.…”
Section: Discussionmentioning
confidence: 56%
“…In a study conducted by Muralidhara et al in 86 PCOS patients, they found that 33% had FBS >100mg%, PPBS were high in about 25% and impaired glucose tolerance was reported by 17%. 10 In obese women, excess insulin and androgens may contribute to the development of the PCOS and metabolic syndrome. The android pattern of fat distribution may be the result as well as the cause of hyperandrogenism, setting up a vicious circle of hyperinsulinism, hyperandrogenism, central adiposity and metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%